The ideal educational model from a historical perspective of pesantren: A case study of futuhiyyah - Mohammad Farhan Zeb Khan; Aliwan; Moch Choirudin; Slamet Panuntun; Abdul Hakim (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2024)
This study aims to examine pesantren education as an ideal educational system model from a historical perspective in the Nusantara region, with a focus on the Futuhiyyah Islamic Boarding School in Mranggen, Demak Regency. Pesantren have long played a vital role in the history of Islamic education in Indonesia, particularly in shaping generations that are not only intellectually capable but also spiritually and socially strong. This research employs a descriptive qualitative approach through literature review and analysis of educational practices in pesantren. The findings indicate that Futuhiyyah develops an integrated educational system that harmoniously combines the teaching of classical Islamic texts (kitab kuning), Islamic values, and the national curriculum. Core values instilled include sincerity, independence, simplicity, discipline, brotherhood, and spirituality. Furthermore, the pesantren has successfully adapted to changing times by utilizing technology and undergoing institutional transformation while maintaining its Islamic identity. Thus, the education system at Futuhiyyah represents an ideal, contextual, and sustainable educational model for shaping the The Perfect Human in the modern era. These findings enrich the discourse on the history of Islamic education and offer an alternative model for developing a national education system rooted in local and spiritual values.